2017
DOI: 10.3201/eid2308.170222
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Baylisascaris procyonis Infection among Humans, Santa Barbara County, California, USA, 2014–2016

Abstract: Baylisascaris procyonis (raccoon roundworm) infection is common in raccoons and can cause devastating pathology in other animals, including humans. Limited information is available on the frequency of asymptomatic human infection. We tested 150 adults from California, USA, for B. procyonis antibodies; 11 were seropositive, suggesting that subclinical infection does occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Zoological institutions can serve as surveillance locales providing information regarding the potential risk of B. procyonis to surrounding communities. Seroprevalence surveys of non-human primates from zoos and people working in wildlife rehabilitation facilities, suggest exposure to B. procyonis without overt clinical disease occurring ( Sapp et al, 2016 ; Weinstein et al, 2017 ; Zimmerman, Dangoudoubiyam & Kazacos, 2019 ). Zoological institutions are the perfect One Health intersection of humans, animals, and their environment and can provide invaluable information regarding diseases of public health importance, such as B. procyonis .…”
Section: Discussionmentioning
confidence: 99%
“…Zoological institutions can serve as surveillance locales providing information regarding the potential risk of B. procyonis to surrounding communities. Seroprevalence surveys of non-human primates from zoos and people working in wildlife rehabilitation facilities, suggest exposure to B. procyonis without overt clinical disease occurring ( Sapp et al, 2016 ; Weinstein et al, 2017 ; Zimmerman, Dangoudoubiyam & Kazacos, 2019 ). Zoological institutions are the perfect One Health intersection of humans, animals, and their environment and can provide invaluable information regarding diseases of public health importance, such as B. procyonis .…”
Section: Discussionmentioning
confidence: 99%
“…Additional cases have been identified in Germany, Austria, and the United Kingdom Curragh et al, 2018). Furthermore, recent evidence lends strong support to the existence of asymptomatic seroconversion; multiple studies have demonstrated 7% seroprevalence of B. procyonis in various subpopulations (children, wildlife rehabilitators, and healthy adults) all of whom were clinically asymptomatic (Brinkman et al, 2003;Weinstein et al, 2017). However, it is unclear whether these individuals were only exposed to the parasite, representing historic or cleared infections, or if ongoing subclinical infections exist.…”
Section: Disease In Humansmentioning
confidence: 97%
“…Tissue damage and clinical outcomes of baylisascariasis might be severe; permanent neurologic sequalae and death might occur because of the large size of B. procyonis larvae and invasive tissue migration ( 3 ). Severity of disease is related to host size, number of eggs ingested, larval migration pathway, and extent of host inflammatory responses ( 4 , 5 ). As with other parasite larva migrans, B .…”
mentioning
confidence: 99%
“…As with other parasite larva migrans, B . procyonis larvae are found mostly in muscle tissue; <5% of migrating larvae reach the brain ( 5 ). Asymptomatic and subclinical infections are known to occur.…”
mentioning
confidence: 99%
See 1 more Smart Citation